The Effects of Energy Price Changes: Heterogeneous Welfare Impacts, Energy Poverty, and CO2 Emissions in Indonesia - Sebastian Renner; Jann Lay; Michael Schleicher (German Institute of Global and Area Studies (GIGA), 2017)
We study the welfare, energy poverty, and CO2 emission implications of energy price change scenarios in Indonesia. Our analysis extends previous analyses of energy price impacts at the household level in several ways. First, by employing a household energy demand system (QUAIDS), we are able to distinguish between first- and second-order welfare effects over the income distribution. Our analysis shows considerable heterogeneity of welfare impacts. For gasoline and electricity, first-order calculations overestimate welfare effects by 10 to 20 per cent for price changes between 20 and 50 per cent. Second, our results point to the ownership of energy-processing durables as another source of impact heterogeneity. Poor households that own these goods may be hit particularly strongly by energy price increases. Third, we extend the welfare analysis beyond the money-metric utility effects and look at energy poverty, which is understood as the absence of or imperfect access to reliable and clean modern energy services. Drawing on the estimated demand function, we find that price increases have substantial effects on energy poverty. Fourth, our analysis explicitly considers the emissions effects of energy price scenarios. We find that reduced household energy demand implies a substantial reduction in emissions. The analysis thus indicates that energy prices may serve as an effective mitigation instrument but also have important adverse welfare effects. The latter can, however, be mitigated by appropriate compensation policies.
Keywords: 300; energy subsidies; climate policy; poverty; distributional effects; energy poverty